Responding to COVID-19: The UW Medicine Information Technology Services Experience - Grange, Elisha S.; Neil, Eric J.; Stoffel, Michelle; Singh, Angad P.; Tseng, Ethan; Resco-Summers, Kelly; Fellner, B. Jane; Lynch, John B.; Mathias, Patrick C.; Mauritz-Miller, Kristal; Sutton, Paul R.; Leu, Michael G. (Applied Clinical Informatics, 2020)
Background UW Medicine was one of the first health systems to encounter and treat COVID-19 patients in the United States, starting in late February 2020.Objective Here we describe the rapid rollout of capabilities by UW Medicine Information Technology Services (ITS) to support our clinical response to the COVID-19 pandemic and provide recommendations for health systems to urgently consider, as they plan their own response to this and potentially other future pandemics.Methods Our recommendations include establishing a hospital incident command structure that includes tight integration with IT, creating automated dashboards for incident command, optimizing emergency communication to staff and patients, and preparing human resources, security, other policies, and equipment to support the transition of all nonessential staff to telework.We describe how UW Medicine quickly expanded telemedicine capabilities to include most primary care providers and increasing numbers of specialty providers. We look at how we managed expedited change control processes to quickly update electronic health records (EHR) with new COVID-19 laboratory and clinical workflows. We also examine the integration of new technology such as tele–intensive care (ICU) equipment and improved integration with teleconferencing software into our EHR. To support the rapid preparation for COVID-19 at other health systems, we include samples of the UW Medicine's COVID-19 order set, COVID-19 documentation template, dashboard metric categories, and a list of the top 10 things your health care IT organization can do now to prepare.Conclusion The COVID-19 response requires new and expedited ways of approaching ITS support to clinical needs. UW Medicine ITS leadership hope that by quickly sharing our nimble response to clinical and operational requests, we can help other systems prepare to respond to this public health emergency.
Keywords: COVID-19; health information technology; public health